Living with Risk and Pressure: Exploring Psychological Well-Being of Coal Mining Workers - Patria Mukti; Joniarto Parung; Artiawati Artiawati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Coal mining employees work in high-risk environments, face long working hours, and experience limited interaction with their families, conditions that potentially affect their psychological well-being. However, empirical understanding of how workers construct and experience psychological well-being within this context remains limited. This study aims to explore the personal experiences and individual meanings of psychological well-being among coal mining employees, describe the factors influencing it, and identify coping mechanisms used to maintain or enhance it. The research design/methodology used an interpretative phenomenological approach. Semi-structured interviews were conducted to collect data, which were analyzed using Interpretative Phenomenological Analysis (IPA). The informants were permanent employees, married, and working as temporary employees. The findings reveal: 1) an in-depth understanding of how coal mining workers define and experience psychological well-being, 2) several factors influencing psychological well-being, including family-health, organizational facilities, connection with family, and work duration. The practical implications of this study indicate that organizations need to place greater emphasis on employees’ psychological well-being, particularly those working far from their families. At the individual level, employees are encouraged to develop adaptive coping strategies, while at the organizational level, psychological support programs and evaluation of working hours are required to better safeguard employee well-being. Keywords: psychological well-being, mining employees, phenomenology